2011
DOI: 10.5539/ies.v4n1p172
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education and Career Intentions of Tertiary Education Students in Akwa Ibom and Cross River States, Nigeria

Abstract: This paper explores the impact of entrepreneurship education on career intentions among 500 students drawn from two universities in Akwa Ibom and Cross River States of Nigeria. The study adopted a survey design. Two research questions and two hypotheses were raised for the study. Data were collected using a structured questionnaire titled Entrepreneurship Education and Career Intentions Questionnaire (EECIQ). The data collected were analyzed using frequency counts, percentages and population t-test. Findings h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 14 publications
3
55
0
3
Order By: Relevance
“…Supporting the current result, Noel (2001) also reported that students with ISSN 2377-4622 2017 entrepreneurship knowledge scores high in entrepreneurial intention and self-efficacy than students of other disciplines. Various other studies in different settings have also shown that there is a significant relationship between entrepreneurship education and entrepreneurial career intention (Ekpoh & Edet, 2011;Wilson et al, 2007). Another study by Fatoki (2014) also reported that students who studied business have a higher level of entrepreneurial intention.…”
Section: Courses Studied and Entrepreneurial Intentionmentioning
confidence: 85%
See 1 more Smart Citation
“…Supporting the current result, Noel (2001) also reported that students with ISSN 2377-4622 2017 entrepreneurship knowledge scores high in entrepreneurial intention and self-efficacy than students of other disciplines. Various other studies in different settings have also shown that there is a significant relationship between entrepreneurship education and entrepreneurial career intention (Ekpoh & Edet, 2011;Wilson et al, 2007). Another study by Fatoki (2014) also reported that students who studied business have a higher level of entrepreneurial intention.…”
Section: Courses Studied and Entrepreneurial Intentionmentioning
confidence: 85%
“…Also, Kolvereid and Moen (1997) found graduates with an entrepreneurship major have stronger entrepreneurial intentions than other graduates. Similarly, other studies have also showed a significant relationship between entrepreneurship education and entrepreneurial career plan (Ekpoh & Edet, 2011;Wilson, Kickul, & Marlino, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The problem is further worrisome with evidence that most educated graduates in the Nigerian labour force are best suited for white-collar jobs; they do not possess the relevant vocational abilities that enable engagement in entrepreneurship (Olorundare and Kayode 2014). This deficiency in the educational system spurred the Nigerian Universities Commission (NUC) to draft a curriculum on entrepreneurship studies for Nigerian universities in 2004 (Ekpoh and Edet 2011). Aside government efforts to encourage entrepreneurship in Nigerian universities, the low-income status of the majority of the Nigerian populace has the tendency to compel student's engagement in entrepreneurial activity as a form of income support.…”
Section: Introductionmentioning
confidence: 99%
“…Ekpoh and Edet [30] conducted a study on entrepreneurship education and career intentions of tertiary education students in Akwa Ibom and Cross River States, Nigeria. The data was collected from 500 students from two universities in Akwa Ibom and Cross River States of Nigeria.…”
Section: Entrepreneurship Education and Career Intentionmentioning
confidence: 99%